COMPUTATIONAL ANALYSIS OF ABIOTIC STRESS INDUCIBLE GENES AND PROTEINS FROM RICE (ORYZA SATIVA L.) - SUPRATIM BASU,; ARYADEEP ROYCHOUDHURY, (International Journal of Pharma and Bio Sciences, 2014)
In this communication, various in silico based prediction tools were employed to localize various stress-inducible genes [dehydrin (viz., RAB16A), polyamine-biosynthesis enzyme (viz., SAMDC), transcription factors (OSBZ8, NAC1, DREBP2, CRT/DRE-BP, WRKY24/51/71), ion channels and membrane transporters (HKT1, NHX1, SOS3) and protein kinases (SAPK5/7)] on rice chromosomes and establish their exon-intron organization, characterize the upstream sequences of these genes or analyze the regulatory domains in the upstream regions. The selected genes were found in seven of the 12 rice chromosomes. A comparative search for the conserved elements in the 5’upstream region of these genes revealed fourteen common and most frequent relevant potential regulatory motifs. Their significance was evaluated by searching for their presence in transcription factor binding site databases. In addition, bioinformatic tools were used to determine the amino acid composition, signal sequences and secondary structures of the corresponding proteins; their subcellular localization, phosphorylation sites and relative solvent accessibility, i.e., percentage of solvent exposed residues. The positional information of these motifs would provide a basis for designing in vivo experiments for more accurate promoter function annotation and in validating the expression of these genes/proteins during abiotic stress in rice.